Estudio de factibilidad para la creación de una clínica terapéutica dedicada a la rehabilitación de personas con adicción activa a sustancias estupefacientes y psicotrópicas, ubicada en la ciudad de Quito, Zona del Valle de los Chillos. - Clavijo Mejía, Nelson Enrique (2013)
This study aims determine the feasibility of implementing a clinic that provides rehabilitation service for people in active addiction to the consumption of narcotic and psychotropic substances, located in the city of Quito, in the Valle de los Chillos zone; considering a social and economic context for its beneficiaries. The chapter number one fully develops the areas relating to market analysis, service analysis, market structure, demand study, study competitors, processing and interpretation of the primary information, among other; also were developed four elements of the marketing mix supplemented with the intangibility, inseparability, perishability and heterogeneity of service.